IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) MODEL WITH THE ASSISTANCE OF MEDIA POSTERS TO IMPROVE LEARNING OUTCOMES IN CLASS XI IPA OF SMA NEGERI 1 PABERIWAI - Anggry Yusna Aslilan Ana Hida; Vidriana Oktoviana Bano (JURNAL EDUSCIENCE, 2023)
The purpose of this research is to describe the learning outcomes of students after applying the Problem Based Learning (PBL) learning model with the help of poster media to improve learning outcomes. This research is a class action research PTK, the Kurt Lewin model, with a quantitative descriptive approach. The research consisted of pre-cycle activities, cycle I and cycle II. The research subjects were students of class XI IPA SMA Negeri 1 Paberiwai TA 2022/2023, totaling 23 people. Pre-cycle, students who complete 30%, cycle I 43% and cycle II 83%. In the affective domain stage I, the predicate was very high, 5 students, the predicate was 12 students, the predicate was low, 6 students, and it increased in cycle II to reach the predicate high, 21 students and the predicate being 2 students. It can be concluded that the application of the Problem Based Learning (PBL) learning model assisted by poster media can improve student learning outcomes at SMA Negeri 1 Paberiwai. AbstrakTujuan penelitian ini untuk mendeskripsikan hasil belajar peserta didik setelah menerapkan model pembelajaran Problem Based Learning (PBL) berbantuan media poster untuk meningkatkan hasil belajar. Penelitian ini merupakan penelitian tindakan kelas PTK, model kurt lewin, dengan pendekatan deskriptif kuantitatif. Penelitian terdiri dari kegiatan prasiklus, siklus I dan siklus II. Subjek penelitian adalah peserta didik kelas XI IPA SMA Negeri 1 Paberiwai TA 2022/2023, berjumlah 23 peserta didik. Prasiklus, peserta didik yang tuntas 30%, siklus I 43% dan siklus II 83%. Pada ranah afektif tahap siklus I predikat sangat tinggi 5 peserta didik, predikat sedang 12 peserta didik, predikat rendah 6 peserta didik dan mengalami peningkatan pada siklus II mencapai predikat tinngi 21 peserta didik dan predikat sedang 2 peserta didik. Dapat disimpulkan bahwa penerapan model pembelajaran Problem Based Learning (PBL) berbantuan media poster dapat meningkatkan hasil belajar peserta didik di SMA Negeri 1 Paberiwai.Kata Kunci: Model Pembelajaran, PBL, Hasil Belajar, Poster